Biomimetic nanoreactor for targeted cancer starvation therapy and cascade amplificated chemotherapy. (July 2021) - Shao, Fengying; Wu, Yafeng; Tian, Zhaoyan; Liu, Songqin
Abstract: Consuming glucose by glucose oxidase (GOx) has attracted great interest in cancer starvation therapy, but the therapeutic effect is severely limited by the tumor hypoxia environment. Herein, to overcome such limitation, cancer cell membranes disguised biomimetic nanoreactors were elaborately established for synergetic cancer starvation therapy and cascade amplificated hypoxia activated chemotherapy. Via a metallothionein-like self-assembly and infiltration approach, GOx and hypoxia activated prodrug banoxantrone (AQ4N) were efficiently loaded into metal-organic framework ZIF-8 nanocarriers to yield nanoreactor AQ4N/GOx@ZIF-8. Subsequently, the biomimetic nanoreactor (AQ4N/GOx@ZIF-8@CM) was obtained by camouflaging the nanoreactor with cancer cell membrane, which endowed the biomimetic nanoreactor homotypic targeting, immune escape and prolonged blood circulation features. Once targeted accumulating into tumor sites, the acid environment triggered the decomposition of ZIF-8, then encapsulated GOx and AQ4N were released. GOx would rapidly exhaust endogenous glucose and O2 to shut off the energy supply of tumor cells for starvation treatment. Furthermore, the aggravated tumor intracellular hypoxia environment would activate the cytotoxicity of AQ4N for chemotherapy. In vitro and in vivo results demonstrated that the designed biomimetic nanoreactor exhibited negligible systemic toxicity, besides, the combination of starvation therapy and cascade amplified hypoxia activated chemotherapy significantly inhibited the tumor growth and improved the therapeutic efficacy.